Developing Hospital Services Based on "Service Excellence" at the Pantura Regional Hospital, M.A. Sentot Patrol, Indramayu Regency - Zulkifli, Irwan; Agus Aribowo; Ezra Karamang (Ilmu Ekonomi Manajemen dan Akuntansi, 2026)
The advancement of the information age, increasing public awareness, and increasingly fierce competition among healthcare facilities have changed the public's assessment of hospitals. Excellent service is a key factor in increasing patient and family trust and satisfaction with hospitals. With increasing public expectations and intense competition among healthcare facilities, hospitals are required to excel not only in medical services but also in the quality of non-medical services. This study aims to assess and formulate the development of a service excellence-based service system at Pantura M.A. Sentot Patrol Regional Hospital, Indramayu Regency. The study used a quantitative approach with a survey method through the distribution of questionnaires to more than 200 respondents consisting of patients and their families. Data analysis showed that communication, staff empathy, speed of service, and facility comfort significantly influence patient satisfaction levels. Based on these findings, this study recommends strengthening excellent service training, developing patient-oriented standard operating procedures (SOPs), and implementing continuous service evaluations. The implementation of these strategies is expected to increase patient satisfaction and loyalty while strengthening the hospital's positive image. The research results are expected to form the basis for recommendations in strengthening excellent service training, formulating SOPs that are oriented towards patient needs, and ongoing evaluation to increase patient satisfaction and loyalty and strengthen the positive image of the hospital.